Republic of Croatia : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that Croatia experienced solid growth in the last two years, with growth rates of about 4 percent exceeding those of the euro area and of many other transition countries. The recovery, initially propelled by private consumption and exports, has more recently extended to investment, encouraged by easy access to credit and public infrastructure spending. After decelerating at the end of 2001 in the wake of the slowdown in Europe, growth resumed strongly in the first quarter of 2002 supported by domestic demand. The outlook for 2002 is moderately positive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet